LEMBAGA ADAT SEBAGAI UPAYA PENGUATAN RESTORATIVE JUSTICE DI DESA DASPETAH KABUPATEN KEPAHIANG - Bambang Sugianto; Windi Arista; Muhammad Nur Amin; Rusmini Rusmini (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Daspetah Village, as the oldest and largest village in Ujanmas Subdistrict, Kepahiang Regency, has high social dynamics due to its large and heterogeneous population. The high level of social and economic activity among the community has led to various conflicts and violations of the law, such as fights, theft, and violence. Until now, conflicts have been resolved through deliberation, the police, or the courts, which often result in wasted time and money. The enactment of Law Number 1 of 2023 concerning the Criminal Code, which recognizes customary law as living law, opens up opportunities for the optimization of dispute resolution through non-litigation mechanisms based on customary law. This community service activity aims to establish and strengthen the Kutei Village Customary Institution as an institution for conflict resolution based on restorative justice. The method used is Participatory Action Research (PAR) through the stages of preparation, socialization, assistance, and evaluation, involving the village government, traditional leaders, religious leaders, and the community. The results of the activity show the formation of the Kutei Desa Customary Institution, which has legal standing based on Article 18B paragraph (2) of the 1945 Constitution, Law Number 6 of 2014 concerning Villages, and Kepahiang Regency Regulation Number 11 of 2016 concerning Rejang Kepahiang Customary Law. This institution has the authority to resolve customary disputes and minor violations through deliberation, mediation, and the imposition of customary sanctions using a restorative justice approach. The existence of the Kutei Desa Customary Institution has proven to have the support of the community and contributes to the resolution of conflicts in a more effective and fair manner, while preserving local wisdom values. Strengthening the capacity of customary leaders and sustainable mediation strategies are recommended to ensure the optimization of the role of customary institutions in a transparent and fair village legal system.